Mensuração sob a perspesctiva dos custos logísticos: estudo de caso em uma empresa de transporte público ferroviário - Vasconcelos, Vitória Maria Mola de (2015)
closely related to the operational complexity of the market requirements. In this scenario, measure and control the logistic costs represent a source for competitive advantage and cost reductions. The company studied in this work is part of the passenger transport sector and, although it is subsidized, it still requires operational and financial improvements to ensure its operational sustainability. To this end, it was decided to measure the costs based on the logistics perspective. In this way, a literature review was performed to identify the main factors that imply in logistic costs. The methods RKW and ABC were used to compute these costs, generating data coherent to the main objective, and tailoring its steps according to the company characteristics. Finally, it was verified that the logistic costs in the studied company represents 36,5% of total costs. Although the literature points out that logistic costs usually represent 10% of total costs, the obtained value is compatible, once the company is a service provider, and large portion of (labor) costs are related to the implementation of logistic activities. Conceptually, the methods applied were compatible with the primary objective of the study, allowing the identification and measurement of the logistic costs. The achievement of this objective simplify the activity of cost control, allowing better targeting the actions to reduce them.